Nephroprotective effect of dapagliflozin in type 2 diabetes mellitus: A potential role of Klotho protein - I. Topchii; P. Semenovykh; V. Galchiskaya; K. Savicheva (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. The present study aimed to investigate the dynamics of clinical and laboratory parameters and serum Klotho protein level in patients with diabetic kidney disease using nephroprotective therapy combined with an inhibitor of the sodium-glucose cotransporter 2 (SGLT2) dapagliflozin.Methods. A total of 76 type 2 diabetic patients with diabetic nephropathy (DN) were examined in this prospective study. Control group - 20 healthy subjects. 53 patients received a standard course of treatment, which included metformin, renin-angiotensin-aldosterone system blockers and statins. In addition to standard therapy, 23 patients have been prescribed the SGLT2 inhibitor dapagliflozin 10 mg per day. The treatment follow-up period was six months. Klotho concentration was determined by an enzyme-linked immunosorbent assay.Results. The development of DN in type 2 diabetic patients was accompanied by a significant decrease in soluble Klotho protein in comparison with controls and patients without nephropathy. During follow-up, Klotho protein level was changed significantly in the group of DN patients with albuminuria. Standard therapy resulted in Klotho concentration increase by 14% compared to pre-treatment values; a more demonstrative increase in the Klotho level was found in the dapagliflozin group (almost 23%).Conclusions. SGLT2 inhibitor treatment resulted in a significant increase of pleiotropic serum protein Klotho in patients with type 2 diabetes and diabetic kidney disease.